Effectiveness of Model Problem Based Learning with Video in Learning Imun System Materials in SMA N 1 Semarang - Aulia, Ike Nur; Pukan, Krispinus Kedati; Widiyaningrum, Priyantini (FMIPA UNNES, 2019)
Problem based learning (PBL) with video can be the concept of student knowledge on immune system material. The PBL 2013 model is widely used in learning or curriculum, but implementation is rarely used in learning. Based on preliminary observation at SMA N 1, it is known that the absorption capacity of immune system is 21.91% at national exam is the lowest. This research on the effectiveness of problem-based learning models with videos on student learning results in cognitive, affective and psychomotor aspects. The research sample consists of three experimental classes. Data sources include students' cognitive learning outcomes (pretest-posttest), affective learning outcomes, psychomotor learning outcomes, teacher qualitative descriptive analysis (interview) and student responses with descriptive percentage analysis. Data were analyzed by using the cognitive learning outcomes (pretest-posttest) in experimental classes. The questionnaire of learning implementation shows that the PBL with video on the immune learning system has been done well. The calculation of the N-gain value, the experimental classes has been increased by 0.77 with the high category. Based on the results of the research, it can be concluded that the PBL model for students is effective in applying material to cognitive, affective and psychomotor learning outcomes of students in SMA N 1 Semarang.